Vivienda, función social y cesión de uso obligatoria a partir de la Sentencia del Tribunal Constitucional núm. 120/2024, de 8 de octubre - Alicia Beundía Méndez (Revista Vasca de Administración Pública)
This paper aims to analyze the majority opinion and the dissenting opinions expressed by Judges Ricardo Enríquez Sancho, Enrique Arnaldo Alcubilla, Concepción Espejel Jorquera and César Tolosa Tribiño in Constitutional Court Judgment no. 120/2024, of October 8, based on the substantive configuration of the constitutional right to the enjoyment of decent and adequate housing. In this context, the analysis focuses on the systematization of the different legislative mechanisms for the mobilization of the vacant housing stock, with special reference to the study of the nature and scope of the partial compulsory expropriation consisting of the temporary transfer of use in favour of the Public Administration for the destination of the housing to its social function through the rental regime, and its interaction with the material guarantees that homeowners are entitled to under Article 33 of the Spanish Constitution.